Increased prescribing trends of paediatric psychotropic medications. Issue 12 (19th November 2004) - Wong, I C K; Murray, M L; Camilleri-Novak, D; Stephens, P
Abstract : Psychotropic medication use by children in the USA has increased. We used the IMS MIDAS Prescribing Insights to examine prescribing trends in nine countries between the years 2000 and 2002. Trends in seven countries rose significantly from year 2000 to 2002; the UK had the highest increase (68%).